Compensation regulation and political promotion of executives of state-owned enterprises: Quasi-natural experiment based on the reform of compensation regulation in China - Jun Bai; Chuang Li; Shasha Li; Weiting Luo (China Journal of Accounting Studies (CJAS), 2021)
Using a sample of listed state-owned enterprises in China from 2013 to 2018, this paper focuses on the impacts of compensation regulation policy on the changes of incentive mode for SOE executives. We find that after the policy, the compensation incentive channel for highly-paid executives has been replaced by political promotion as an alternative incentive mechanism. Further analysis shows that ingratiatory behaviour has become the main channel for SOE executives to seek promotion after the policy. Our results provide support for the relationship hypothesis relating to the political promotion of SOE executives, and such effects are more pronounced within younger SOE executives with lower enterprise level and marketisation degree. Finally, we find that the existence of alternative benefit acquisition channels such as equity incentive, perquisite consumption and the degree of mixed ownership reform of SOE has weakened the relationship between compensation regulation and political promotion of SOE executives.
Keywords: 650; compensation incentive; Compensation regulation; performance hypothesis; political promotion; Quasi-natural experiment; relationship hypothesis